By LearningExpress Editors
Updated on Oct 9, 2013
To review these concepts, go to Polynomials and Multiplying Binomials Study Guide.
Polynomials and Multiplying Binomials Practice Questions
Practice
Find the product of each binomial.
- (x + 2)(x + 3)
- (2x –1)(x –5)
- (3x + 7)(6x – 10)
- (–x + 3)(8x + 15)
- (7x + 2)(2x + 4)
- (x + 9)(9x –8)
- (x – 8)^{2}
- (3x + 2)^{2}
- (x + 10)(x – 10)
- (5x – 12)(5x + 12)
Solutions
1. | Use FOIL and combine like terms: |
First: (x)(x) = x^{2} | |
Outside: (x)(3) = 3x | |
Inside: (2)(x) = 2x | |
Last: (2)(3) = 6 | |
x^{2} + 3x + 2x + 6 = x^{2} + 5x + 6 | |
2. | Use FOIL and combine like terms: |
First: (2x)(x) = 2x^{2} | |
Outside: (2x)(5) = –10x | |
inside: (–1)(x) = –x | |
Last: (–1)(–5) = 5 | |
2x^{2} – 10x – x + 5 = 2x^{2} – 11x + 5 | |
3. | Use FOIL and combine like terms: |
First: (3x)(6x) = 18x^{2} | |
Outside:(3x)(–10) = –30x | |
Inside: (7)(6x) = 42x | |
Last: (7)(–10) = –70 | |
18x^{2} – 30x + 42x – 70 = 18x^{2} + 12x – 70 | |
4. | Use FOIL and combine like terms: |
First:(–x)(8x) = –8x^{2} | |
Outside: (–x)(15) = –15x | |
Inside: (3)(8x) = 24x | |
Last: (3)(15) = 45 | |
–8x^{2} – 15x + 24x + 45 = – 8x^{2} + 9x + 45 | |
5. | Use FOIL and combine like terms: |
First: (7x)(2x) = 14x^{2} | |
Outside: (7x)(4) = 28x | |
Inside: (2)(2x) = 4x | |
Last: (2)(4) = 8 | |
14x^{2} + 28x + 4x + 8 = 14x^{2} + 32x + 8 | |
6. | Use FOIL and combine like terms: |
First: (x)(9x) = 9x^{2} | |
Outside: (x)(–8) = –8x | |
Inside: (9)(9x) = 81x | |
Last: (9)(–8) = 72 | |
9x^{2} – 8x + 81x – 72 = 9x^{2} + 73x – 72 | |
7. | Because (x –8) is raised to the second power, multiply it by itself: (x –8)2 = (x –8)(x –8). Use FOIL and combine like terms: |
First: (x)(x) = x^{2} | |
Outside: (x)(–8) = –8x | |
Inside: (–8)(x) = –8x | |
Last: (–8)(–8) = 64 | |
x^{2} – 8x – 8x + 64 = x^{2} – 16x+ 64 | |
8. | Because (3x + 2) is raised to the second power, multiply it by itself: (3x + 2)2 = (3x + 2)(3x + 2). Use FOIL and combine like terms: |
First: (3x)(3x) = 9x^{2} | |
Outside: (3x)(2) = 6x | |
Inside: (2)(3x) = 6x | |
Last: (2)(2) = 4 | |
9x^{2} + 6x + 6x + 4 = 9x^{2} + 12x + 4 | |
9. | Use FOIL and combine like terms: |
First: (x)(x) = x^{2} | |
Outside: (x)(–10) = –10x | |
inside: (10)(x) = 10x | |
Last: (10)(–10) = –100 | |
x^{2} – 10x + 10x – 100 = x^{2} – 100 | |
10. | Use FOIL and combine like terms: |
First: (5x)(5x) = 25x^{2} | |
Outside: (5x)(12) = 60x | |
Inside: (–12)(5x) = –60x | |
Last: (–12)(12) = –144 | |
25x^{2} + 60x – 60x – 144 = 25x^{2} – 144 |
From Algebra in 15 Minutues A Day. Copyright © 2009 by LearningExpress, LLC. All Rights Reserved.
Post a Comment
| No comments so far
Ask a Question
Have questions about this article or topic? Ask150 Characters allowed
Related Questions
See More QuestionsPopular Articles
Wondering what others found interesting? Check out our most popular articles.
- Kindergarten Sight Words List
- First Grade Sight Words List
- 10 Fun Activities for Children with Autism
- Grammar Lesson: Complete and Simple Predicates
- Definitions of Social Studies
- Child Development Theories
- Signs Your Child Might Have Asperger's Syndrome
- How to Practice Preschool Letter and Name Writing
- Social Cognitive Theory
- Theories of Learning